2023
DOI: 10.1136/bmjopen-2022-068915
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions of non-statin antihyperlipidaemic drugs in China from 1989 to 2019: a national database analysis

Abstract: ObjectiveThis study aims to understand the adverse drug reactions (ADRs) for non-statin antihyperlipidaemic drugs included in the China Anti-hyperlipidemic Drug Database.DesignAn approach of Chinese national database analysis was employed to screen clinical trials involving non-statin antihyperlipidaemic drugs from 1989 to 2019.SettingThe database was provided by the China National Medical Products Administration Information Centre.ParticipantsIn total, 117 clinical studies with 8800 patients were selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Probucol is the only antioxidant drug approved by Food and Drug Administration, and it also shows a very powerful therapeutic effect in CVDs, but it has gradually faded out of the clinical treatment of CVDs because of its side effects such as gastrointestinal discomfort, diarrhea, ventricular tachycardia and severe ventricular arrhythmias [ 309 , 310 ]. Although antioxidants have not been widely used in the treatment of CVDs to date, they should still be taken seriously, especially natural antioxidants, which remain indispensable as potential therapeutic agents for the treatment of CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Probucol is the only antioxidant drug approved by Food and Drug Administration, and it also shows a very powerful therapeutic effect in CVDs, but it has gradually faded out of the clinical treatment of CVDs because of its side effects such as gastrointestinal discomfort, diarrhea, ventricular tachycardia and severe ventricular arrhythmias [ 309 , 310 ]. Although antioxidants have not been widely used in the treatment of CVDs to date, they should still be taken seriously, especially natural antioxidants, which remain indispensable as potential therapeutic agents for the treatment of CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 More rarely, fibrates have been associated with an increased risk of cholesterol gallstones, pancreatitis, venous thromboembolism, and pulmonary embolism, although all are uncommon. [56][57][58][59][60][61] The most serious adverse events from fibrates are renal dysfunction, myopathy, and liver injury. A systematic review of 37 studies involving 1,107 patients with cholestatic liver disease (PBC and primary sclerosing cholangitis), treated with both UDCA and fibrates, found that the types of adverse events experienced with these medications were the same as those reported in patients without cholestatic disease, and occurred at similar rates.…”
Section: The General Safety Of Fibratesmentioning
confidence: 99%